Organised Fruit and Vegetable Marketing Channels in Andhra Pradesh - B. Venkat Rao, (Journal of Agricultural Extension Management, 2025)
Marketing of fruits and vegetables has assumed new dimensions with rise in per capita income and health consciousness, mostly in urban areas of India. This study looks at existing Marketing Channels viz., Agricultural Produce Marketing Committees, Rythu Bazaars and organised Private Retail and compares benefits accruing to consumers in Andhra Pradesh. The various dimensions studied include, preferred channel by consumers; quality of produce in different marketing channels; consumer satisfaction with prices; convenience factor; service factor; impact of display; promotionat"advertising and price display on channel preference. According to the study, except for little benefit to consumers, not much benefit has accrued to producers even from Organized Private Retail. However small and medium farmers are benefited through Rythu Bazaars since farmers are able to sell their produce directly to consumers and get a good price. There is a mismatch between demand and supply due to lack of information and knowledge on production, price and market dynamics within and outside India. The study suggests that in order to prevent seasonal glut and ensure price stability throughout the year, the government must take steps to prepare Mandal level plans for agricultural produce, estimate the quality of produce coming to the market, route excess produce to other consumption centers and look into processing and export opportunities. Timely information must be provided to farmers by extension staff to prevent crop loss and ensure good price to the farmers